Conceptualizing The Qatari-African Foreign Policy And Economic Relations: The Case Of Soft Power - O’Bright, Ben (Journal of Sustainable Development Law and Policy, 2025)
Using a case study approach, this article examines the shifting dimensions of Qatar’s international relations strategies with select, geo-politically important African states, including primarily the latter’s private sector and civil society, and focusing on the current or potential use of soft power in particular. To start, this article presents a comprehensive overview of soft power, including its international relations theory-based historical origins; definitional boundaries; associated tools and mechanisms; and the concept’s pragmatic problems and limitations. Second, the article offers several best practice case studies, including the United Kingdom and China, from which core lessons on soft power development and application can be gleaned. This will advance from a list of seven key lessons that any prospective soft power state should consider. Following this, the article engages in an examination of available evidence outlining Qatar’s attempted soft power action on the African continent and, particularly in Sudan, Somalia, Mali and Tunisia, arguing that it relies extensively on “carrotdiplomacy” or the influencing of others backed by material and financial resource inducements. Finally, five problems and roadblocks affecting Qatar’s approach to international relations will be presented, followed by alternative (soft) power-based strategies, which could be explored by its government and leadership.